PENGARUH CITRA MEREK, KUALITAS PRODUK, IKLAN, VARIETY SEEKING, DAN HARGA TERHADAP PERPINDAHAN MEREK KE KOSMETIK WARDAH (Studi Pada Konsumen Bedak Wardah di Sardo Swalayan) - Windy Tri Septiningsih; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACThis study aims to determine the effect of Brand Image, Product Quality, Advertisements, Variety Seeking, and Prices on Brand Transfers partially or simultaneously. The population and sample in this study were 85 people who were consumers of Wardah Powder in Sardo Supermarkets. Data collection through questionnaires. in this study using the help of SPSS version 14 with the data testing techniques used in this study include validity test, reliability test, normality test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis.The results of this study indicate that product quality, advertising, and variety seeking partially have no significant effect on brand displacement while brand image and price have a significant effect on brand displacement. Simultaneously, it shows that brand image, product quality, advertising, variety seeeking, and price influence the brand shift in wardah powder.Keywords: Brand Image, Product Quality, Advertising, Variety seeking, Price and brand transfer